Indirect revascularization vs. non-surgical treatment for Moyamoya disease and Moyamoya syndrome: A comparative effectiveness study - Wang, Yixuan; Li, Miao; Wang, Jie (Frontiers in Neurology, 2022)
Background The efficacy of indirect revascularization vs. non-surgical treatment in adults with Moyamoya disease (MMD) and Moyamoya syndrome (MMS) remains controversial. Objective To compare the clinical outcomes of indirect revascularization and non-surgical treatments in adult patients with MMD and MMS. Methods We collected medical records and follow-up results of adult patients with MMD and MMS who received treatment in the China-Japan Union Hospital of Jilin University between January 2019 and December 2021. A Shapiro–Wilk test, independent sample t-test or Mann-Whitney U-test, and Pearson chi-square test were used to compare baseline variables. The propensity-score analysis was used to compare clinical outcomes of patients with MMD and MMS who underwent indirect revascularization and non-surgical treatments. The color-coded digital subtraction angiography (CC-DSA) was used to quantitatively analyzed the preoperative and postoperative (at 6-month follow-up) images of patients in the surgical group. Results A total of 144 patients were included in this study, of whom 37 received indirect revascularization treatment and 107 received non-surgical treatment. The average age of the patients was 58.3 ± 13.4 years. Perioperative complications were observed in eight of the operations. During the follow-up period, a total of 35 stroke events occurred, including two cases (5.4%) in the surgery group and 33 cases (30.8%) in the non-surgery group (p < 0.05). The preoperative mean transit time (MTT) of bypass vessel (superficial temporal artery, STA) was 0.26 ± 0.07, and the postoperative MTT of bypass vessel was 3.0 ± 0.25, and there was no statistical difference between the subgroups. Conclusion Indirect revascularization surgery can significantly reduce the recurrent stroke incidence of MMD and MMS patients.